Makna dan Relevansi Nilai Kearifan Lokal dalam Tradisi Meron bagi Generasi Z Desa Sukolilo - Rifki Ramanda Rahman; Yusuf Falaq (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
The Meron tradition in Sukolilo Village, Pati Regency, is a unique celebration held to honour the birthday of the Prophet Muhammad SAW. This event resembles the Skatenan ceremony celebrated at the Surakarta and Ngayogyakarta Palaces. For the Gen Z generation, Meron is not just a celebration; it has symbolic meaning and local wisdom that influences various aspects of the lives of villagers. The research used a qualitative approach involving active participation from the Sukolilo community. The study results show that the Meron tradition contains religious, social, artistic, and economic values ??seen in every stage of its implementation. The community plays an active role in preserving Meron by holding annual ceremonies that focus on developing, protecting, and promoting local culture. Furthermore, this tradition instils highly respected ethics, which are important in maintaining sustainability from generation to generation. This ensures that cultural heritage remains preserved and relevant, especially for the Gen Z generation influenced by modern culture. Meron is not just a celebration but an important part of cultural heritage that has eternal value. Efforts to preserve this tradition are significant to maintain the sustainability of traditions in Sukolilo Village in the future.